An Analysis of the Aerosol Lifecycle Over India: COALESCE Intercomparison of Three General Circulation Models. Issue 14 (21st July 2022) - Bhattacharya, Anwesa; Venkataraman, Chandra; Sarkar, Tanmay; Sharma, Amit Kumar; Sharma, Arushi; Anand, S.; Ganguly, Dilip; Bhawar, Rohini; Dey, Sagnik; Ghosh, Sudipta
Abstract: Atmospheric aerosols or atmospheric particulate matter affects climate variables like temperature and rainfall, agricultural productivity, soil, and human health. We evaluated aerosol lifecycle over India via simulations (2005–2014) from three general circulation models under the COALESCE project (carbonaceous aerosol emissions, source apportionment, and climate impacts; Venkataraman et al., 2020, 10.1175/bams‐d‐19‐0030.1). The ECHAM6.3‐HAM2.3, CAM5.3, and NICAM‐SPRINTARS simulations use identical regional emissions (from the Speciated Multi‐pollutant generator, SMoG‐India‐v1). Satisfactory model simulations of meteorological variable magnitudes and seasonal cycle have been achieved partly from the adoption of nudging. Estimations of anthropogenic aerosol, aerosol optical depth (AOD), and particulate matter surface concentrations are significantly improved from (a) dust tuning (b) use of satellite‐derived organic aerosol to carbon ratio, and (c) nudged meteorology to capture variables influencing the production of secondary sulfate. Larger wintertime under prediction (−30% to −60%) results from over prediction of seasonal planetary boundary layer height and the absence of secondary ammonium nitrate and organic aerosols. Vertical dispersion to higher altitudes than in observations calls for improved modeling of vertical mass flux representation. Carbonaceous aerosol residence time and AOD fraction larger than global mean values in India, with a seasonal predominance in the autumn and winter seasons can be explained by enhanced regional emissions from residential biofuel cooking, agricultural stubble burning, and traditional informal industries like brick production. Plain Language Summary: Air pollution, climate change and agricultural productivity are all affected by atmospheric pollutants called aerosols. Models must accurately estimate aerosol particle amounts seasonally, spatially and with altitude to capture their impacts. In this work, we use test and identify approaches to improve aerosol estimation by global climate models over India. We diagnose reasons for model disagreement with observations and suggest some ways to improve them. Larger abundances of carbonaceous aerosols (black carbon or soot, which causes warming and organic aerosol, which has high toxicity) are found over India, than globally, especially in autumn and winter. These result from enhanced regional emissions from residential biofuel cooking, agricultural stubble burning, and traditional informal industries like brick production. They could cause possible near‐term climate warming over India, in contrast to consistent aerosol induced cooling in other world regions. Key Points: Simulated aerosol mass improves from use of a regional emissions inventory, organic aerosol to carbon ratio and dust tuning Model improvements are needed in estimation of vertical mass flux, secondary nitrate and organic aerosol Larger carbonaceous aerosol residence times and AOD fraction over India, than global estimates, result from larger regional emissions